Inhibitory PD-1 axis maintains high-avidity stem-like CD8+ T cells - Jyh Liang Hor; Edward C. Schrom; Abigail Wong-Rolle; Luke Vistain; Wanjing Shang; Qiang Dong; Chen Zhao; Chengcheng Jin; Ronald N. Germain (Nature, 2026)
Abstract Stem-like progenitors are self-renewing cytotoxic T cells that expand as effector cells during successful checkpoint immunotherapy 1,2 . Emerging evidence suggests that tumour-draining lymph nodes support the continuous generation of these stem-like cells that replenish tumour sites and are a key source of expanded effector populations 3–6 , underlining the importance of understanding what factors promote and maintain activated T cells in the stem-like state. Here, using advanced three-dimensional multiplex immunofluorescence imaging, we identify antigen-presentation niches in tumour-draining lymph nodes that support the expansion, maintenance and affinity evolution of TCF-1 + PD-1 + SLAMF6 high stem-like CD8 + T cells. Contrary to the prevailing view that persistent T cell receptor (TCR) signalling drives terminal effector differentiation, prolonged antigen engagement days beyond initial priming sustains the proliferation and self-renewal of these stem-like T cells in vivo. The inhibitory PD-1 pathway has a central role in this process through fine-tuning the TCR signal input that enables the selective expansion of high-affinity TCR stem-like clones as a renewable source of effector cells. PD-1 blockade disrupts this tuning, leading to terminal differentiation or death of the most avid anti-tumour stem-like cells. Our results therefore reveal a relationship between TCR ligand affinity recognition, a key negative-feedback regulatory loop and T cell stemness programming. Furthermore, these findings raise questions about whether anti-PD-1 blockade during cancer immunotherapy provides a short-term anti-tumour effect at the cost of diminishing efficacy due to progressive loss of these critical high-affinity precursors.